Remifentanil attenuates sepsis-induced intestinal injury by inducing autophagy. Issue 2 (20th December 2021) - Wang, Mingli; Guo, Shiqi; Zhang, Yu; Zhang, Yao; Zhang, Hong
ABSTRACT: Remifentanil (RFT), extensively used for general anesthesia, is a synthetic ultra-short-acting opioid used as an anti-inflammatory oxidant to alleviate a plethora of diseases. This study was designed to determine whether RFT would provide protective effects on sepsis-induced intestinal injury.The determination of cell viability and inflammation of LPS-treated IEC-6 cells influenced by RFT was conducted by Cell counting Kit-8 (CCK-8), RT-qPCR, and western blot, while the detection of LDH, diamine oxidase (DAO), and intestinal-type fatty acid binding proteins (I-FABP) was conducted for determining the intestinal cytotoxicity in these cells. The apoptosis of these cells was detected by TUNEL, with autophagy-related protein expression measured by western blot to confirm whether autophagy was activated. Finally, the aforementioned assays were conducted again after 3-Methyladenine (3-MA), an autophagy inhibitor, was used on these cells to investigate whether RFT exerted its effects on LPS-treated IEC-6 cells via modulation of autophagy.RFT alleviates LPS-induced IEC-6 cell inflammation, cytotoxicity and apoptosis, and autophagy-related proteins were expressed at higher levels when RFT was used on these cells. Nevertheless, further treatment of 3-MA weakened the restorative impacts of RFT on the inflammation, cytotoxicity and apoptosis of these cells.To conclude, this paper is the first to present evidence that RFT attenuates sepsis-induced intestinal injury by inducing autophagy, which will provide instructions for the future investigations into the use of RFT in treatment of intestinal injury.